1997
DOI: 10.1111/j.1469-7793.1997.677bm.x
|View full text |Cite
|
Sign up to set email alerts
|

The interplay of central and peripheral factors in limiting maximal O2 consumption in man after prolonged bed rest

Abstract: The effects of bed rest on the cardiovascular and muscular parameters which affect maximal O2 consumption (VO2,max) were studied. The fractional limitation of VO2,max imposed by these parameters after bed rest was analysed. The VO2,max, by standard procedure, and the maximal cardiac output (Q̇max), by the pulse contour method, were measured during graded cyclo‐ergometric exercise on seven subjects before and after a 42‐day head‐down tilt bed rest. Blood haemoglobin concentration ([Hb]) and arterialized blood g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
135
3
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(152 citation statements)
references
References 36 publications
13
135
3
1
Order By: Relevance
“…Skeletal muscles become weaker with less endurance for light physical effort (1). In addition, metabolic pathways adapt to inactivity by decreasing mitochondrial concentration in skeletal muscles (38), lowering the capacity to oxidize fatty acids. Whole body insulin sensitivity declines within the first 3 days of inactivity, whether it is bed rest (65,87) or active individuals stopping daily exercise (15,73).…”
Section: How Does the Body Maladapt To Inactivity?mentioning
confidence: 99%
“…Skeletal muscles become weaker with less endurance for light physical effort (1). In addition, metabolic pathways adapt to inactivity by decreasing mitochondrial concentration in skeletal muscles (38), lowering the capacity to oxidize fatty acids. Whole body insulin sensitivity declines within the first 3 days of inactivity, whether it is bed rest (65,87) or active individuals stopping daily exercise (15,73).…”
Section: How Does the Body Maladapt To Inactivity?mentioning
confidence: 99%
“…These results are in agreement with a recent study by Nielsen et al (48), who showed that SS mitochondrial content decreased by 33% after 2 wk of muscle immobilization by whole leg casting, whereas central IMF mitochondrial content remained unchanged. In contrast, Feretti et al (22) reported a 17% decrease in IMF mitochondria, with no significant decrease in SS mitochondrial content, in young subjects after 37 days of bed rest. The difference in mode of disuse and activity level could explain the observed discrepancies.…”
Section: Discussionmentioning
confidence: 89%
“…It is known that with inactivity (14, 50, 52), immobilization (22,48), and denervation (26,43), muscle oxidative capacity is reduced. The latter has at least partly been attributed to a change in muscle fiber type composition toward more type 2 fibers (54) and in particular type 2x fibers (12,13,57).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in this experimental model, only the duration of the bed rest period varies among studies, allowing a precise evaluation of the time courses of the functional modifications induced by bed rest. _ V O 2max decreases after bed rest (Bringard et al 2010;Capelli et al 2006;Convertino et al 1982;Ferretti et al 1997a;Greenleaf et al 1989;Kashihara et al 1994;Saltin et al 1968;Stremel et al 1976;Trappe et al 2006), even of very short duration (Smorawinski et al 2001). The size of the _ V O 2max decrease is larger the longer is the bed rest duration, being fast in the first days, and progressively slower as bed rest proceeds.…”
Section: Of Maximal Oxygen Consumption At the End Of Bed Restmentioning
confidence: 99%
“…This explains why F Q ¼ 0:7 instead of 0.5, so that we necessarily have F p ¼ 0:3, partly attributable to F t , partly to F m . According to Ferretti et al (1997a), the differences in _ V O 2max would be minimal, if we assume, on one extreme, R t ¼ R p , and on the other extreme, R m = R p , and that it makes no difference to assume R t and R m in series or in parallel. Direct experimental assessment of the parameters of Eq.…”
Section: ð4:5þmentioning
confidence: 99%